Pengaruh Perceived Value Terhadap Kepuasan Tamu Di Grand Buana Lestari Hotel - Nudia Khairiah; Dwi Pratiwi Wulandari (Lembaga Pengembangan Kinerja Dosen, 2024)
Guest expectations are still not in accordance with the facilities offered, lack of interest of guests to visit again, reluctance to recommend the hotel to guests, uncomfortable breakfast atmosphere and efficiency of room service time in fulfillment. . the wishes of the guests. The purpose of this study is to analyze the effect of perceived value on customer satisfaction. The research used in this study is descriptive with quantitative data. The study sample consisted of 122 guests using non-probability sampling. Data was collected using Likert scale. Data is processed with SPSS 25.00. The perception value is in the fairly good category or 47.54%. In addition, the variable of customer satisfaction is in the good category, namely. 46.5% The influence of perceived score (X) affects guest satisfaction (Y), score 11.4% and other factors by 88.6%. The results of multiple linear regression analysis obtained a calculated F value of 1.696 with sig. 0.000 < 0.05, meaning that the perceveid value variable on guest satisfaction has a significant effect, and a t score of 1,302 with SIG is obtained. 0.000 < 0.05